Topical hydrogel human amnion membrane for wounds healing in mice (mus musculus) induced by diabetes - Pakpahan, Suyarta Efrida; Fadhilah, Fitri Rahmi; Amalia, Mia; Putri, Ericha Nurlina (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2025)
Background: One of the complications that occurs in DM patients is the occurrence of chronic wounds. The use of Human Amnion Membrane (hAM) has been identified as a promising natural option for the treatment of skin lesions, including burns and diabetes mellitus. This hAM contains an extracellular matrix (ECM) with components such as growth factors, collagen, and proteoglycans as anti-inflammatory and anti-microbial in wounds. The purpose of this study was to analyze the effect of hAMD hydrogel treatment on wound closure in mice induced by alloxan macroscopically and microscopically on days 3, 7, 14, and 21. Method: This research method, experimental using mice divided into 4 treatment groups, namely negative control (healthy group without treatment, DM without treatment), internal control (DM treatment carbopol) and DM treatment hAMD. Measurement of wound area (macroscopic), histology processing (Hematoxylin Eosin), reading of histology preparations (microscopic) and Two-way ANOVA test analysis using Graphpad Prism 10 was carried out. Results: The results of the study from 4 treatment groups where in the healthy group without treatment on the 21st day the wound closure was complete, the DM group without treatment on the 21st day the wound closure was not yet completely closed, in the DM carbopol treatment group on the 14th day the wound closure was not yet completely closed, and in the DM hAMD treatment group 15% on the 14th day the wound closure had closed completely. This is in line with the results of statistical and histological analysis. Conclusion: The conclusion of this study is that the effect of human amnion membrane hydrogel can heal diabetes mellitus skin wounds faster compared to the control group. Keywords: Diabetes Mellitus, Hydrogel, Extracellular Matrix, Amniotic Membrane.